Study of factors influencing the occurrence of conflicts in pharmacies - Т. P. Zarichna; N. M. Chervonenko; N. O. Brahar (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2024)
The aim of the study was to investigate the factors influencing the occurrence of conflicts in pharmacies during the provision of pharmaceutical care, with the subsequent goal of optimizing the social and psychological climate within the team and improving the quality of service to the population.